2007
DOI: 10.1097/01.ta.0000250497.08101.8b
|View full text |Cite
|
Sign up to set email alerts
|

Fresh Frozen Plasma Should be Given Earlier to Patients Requiring Massive Transfusion

Abstract: These data indicate acidosis and hypothermia to be well managed. Coagulopathy was not corrected in the ICU despite adherence to pre-ICU MT and ICU protocols, likely because of inadequate pre-ICU intervention. More aggressive pre-ICU intervention to correct coagulopathy may be effective in decreasing PRBC requirement during ICU resuscitation, and, because of the association with increased mortality, could improve outcome. We have revised our pre-ICU MT protocol to emphasize early FFP in a FFP:PRBC ratio of 1:1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
314
0
11

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 513 publications
(331 citation statements)
references
References 22 publications
6
314
0
11
Order By: Relevance
“…24,65,66 A balanced approach of all blood components in a 1:1:1 ratio, with the use of RBCs less than 14 days of storage, may be the optimal empiric resuscitation approach for patients with hemorrhagic shock. 7,31,33,42,67,68 Increased plasma transfusion for patients bleeding with traumatic injuries may increase risks associated with its use. Significant risks associated with plasma use include transfusion related acute lung injury and nonhemolytic transfusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…24,65,66 A balanced approach of all blood components in a 1:1:1 ratio, with the use of RBCs less than 14 days of storage, may be the optimal empiric resuscitation approach for patients with hemorrhagic shock. 7,31,33,42,67,68 Increased plasma transfusion for patients bleeding with traumatic injuries may increase risks associated with its use. Significant risks associated with plasma use include transfusion related acute lung injury and nonhemolytic transfusion reactions.…”
Section: Discussionmentioning
confidence: 99%
“…An INR >1.2 was considered indicative of coagulopathy, in accordance with previous studies. [16,17] Missing blood results in the first hour of admission were excluded from the study. The mechanism of injury was obtained from the patient's electronic chart.…”
Section: Researchmentioning
confidence: 99%
“…Civilian and military studies have demonstrated a survival benefit when a close ratio resuscitation of fresh frozen plasma (FFP) to packed red blood cells (PRBC) is used in EPAI. [5][6][7][8][9] Resuscitation strategies in patients with EPAI have evolved throughout the years. Military resuscitation during 1960s used aggressive crystalloid resuscitation with no predefined transfusion ratio of blood component therapy.…”
Section: Introductionmentioning
confidence: 99%
“…This resuscitation strategy has been accepted by many civilian trauma centers with overall improvement in outcomes. [5][6][7][8][9][12][13][14] The etiology leading to this improvement could be multifactorial. During close ratio resuscitation, the goal should consist of FFP matched to PRBC in a 1:1 fashion while minimizing crystalloid utilization.…”
Section: Introductionmentioning
confidence: 99%